AN ANALYSIS ON STUDENTS’ GRAMMATICAL ERRORS IN USING CONDITIONAL SENTENCE TYPE II ON THE THIRD GRADE OF SMA NEGERI 1 PEMATANG SIANTAR IN ACADEMIC YEAR 2023/2024 - Sumiati Butar-Butar; Partohap Saut Raja Sihombing; Mungkap Mangapul Siahaan (CV SWA Anugrah, 2023)
The objectives of this research are to identify and classify the types of error in using conditional sentence type II based on surface strategy taxonomy and to find out the proportions (frequency and percentage) of errors that made by students in using conditional sentence type II at the third grade of SMA Negeri 1 Pematang Siantar. The method of this research was descriptive qualitative research analysis. The researcher chooses 34 of the third grade students of SMA Negeri 1 Pematang Siantar in academic year of 2023/2024. In data collecting, the researcher used test that consist of two parts; part I and part II. In part I, there were ten items where the students were asked to fill the blanks regarding conditional sentence type II. While in part II, the students were asked to create ten examples of conditional sentence type II. The researcher took the data to analyze, percentage, and classify the error based on surface strategy taxonomy. In conclusion, the researcher found four types of error, namely; omission, addition, misformation, and misordering. The students committed total 232 errors in using conditional sentences type II that divided into omission errors with 36 items or 15.52%, adition errors with 37 items or 15.94%, misformation errors with 146 errors or 62.93%, miordering errors with 13 items or 5.61%.